Impacts of training on knowledge dissemination and application among academics in Malaysian institutions of higher education - Dora, Mohd Taib; Hussin, Hanipah; Sidek, Safiah (Canadian Center of Science and Education, 2012)
This paper explores the linkage of knowledge dissemination and the application of new knowledge in teaching and learning practices. A survey data were collected from 519 academics from all the Malaysian public and private institutions of higher learning (IHLs) during the teaching and learning trainings offered by the Academy of Leadership in Higher Education Malaysia, known as the Akademi Kepimpinan Pengajian Tinggi Malaysia (AKePT). Three out of ten behavioral actions were found to have a significant change in behaviors at the workplace: keep-up with the institutional change process,p=0.037, involvement in departmental change, p=0.027 and confidence in decision-making, p=0.037. The seven insignificant behavioral actions were asking peers and colleagues for suggestions, involvement of colleagues in the change process, reluctance in making decisions, holding group meeting, taking time to transform plan into action, and taking time to reflect the consequences of making decisions. These findings raise awareness and provide initial guidelines for AKePT to develop appropriate strategies to ensure that the knowledge dissemination processes lead to the application of new knowledge. further exploration of the formulation of comprehensive strategies to properly implement and manage the knowledge dissemination process among the academics was also suggested. It is also one of the initial studies that highlights the linkages between AKePT's Training Centre and the local teaching and learning training centres. It opens up new lines of future research possibilities on the provision of centralised professional development training programs that facilitate the application of new knowledge at the local teaching and learning context.